#TITLE_ALTERNATIVE# - AULIA DE SILVA NUSANTARA (NIM : 15114072), CANDIDA
Tropical Cyclone Cempaka and Dahlia that occurred some time ago in Indonesia caused a significant impact to area in its path. Although Indonesia is not directly passed by Tropical Cyclones Cempaka and Dahlia, the rainbands of the cyclones have a significant influence on the Indonesian territory. This certainly disturbs activities in the areas such as fishing activities, tourism site, ports, and power plants. This phenomenon can be analyzed from the physical condition especially for tropical cyclones that can be directly caused by Tropical Cyclone Cempaka and Dahlia in Province of Lampung to Bali. This final project has purpose to model wave characteristics in Province of Lampung to Bali with data input from bathymetry and wind data. Wave modeling was performed by numerical method using Simulating Waves Nearshore (SWAN) version 41.20 at the time of Cempaka Tropical Cyclone and Dahlia. The verification process was performed with calculating the correlation coeffiecient and RMSE of significant wave height from wave modeling against significant wave height from altimetry satellite observations across the Tropical Cyclones Cempaka and Dahlia. The increase of wave height is indicated by a percentage of the increase of significant wave height which yields value of up to 678.37% at the observation point in Merak Port.